Symposium 4: Addressing Methodological Issues in e-Learning Research - Conole, Grainne; Oliver, Martin; Isroff, Kim; Ravenscroft, Andrew (Proceedings of the International Conference on Networked Learning, 2004)
As a relative young field, learning technology research suffers in a number of respects (Conole, 2003). Firstly, the area is not yet clearly defined and scoped. Secondly, there is criticism of much of the current research activities, as it is considered too anecdotal, case-based, and lacking theoretical underpinning. Thirdly, as indeed is true in social science research more generally, there are divided views on the importance of quantitative versus qualitative research methods. This paper focuses on the first two of these criticisms. Firstly, an overview of the area will be provided, in response to criticisms of definition and scope. Secondly, a critique of the methodological issues will be given and in particular which methodologies are favoured and why. Thirdly, the criticisms that the area suffers from a lack of theoretical underpinning will be discussed. Finally, the paper concludes by arguing that learning technology research should be articulated within a broader and more holistic socio-cultural framework. The paper provides an overview for the symposium and is followed by three case study papers which take forward these issues by critiquing specific areas and applications of learning technology research. Every discipline has its own epistemological beliefs and associated culture. This consists of three inter-related features. Firstly, the area is shaped by the nature of the research questions being explored. Secondly, it is shaped by the research methodologies adopted and the ways in which these are used to address the research questions. Thirdly, it is shaped by the underpinning theory and theoretical perspectives adopted and used to try and making sense of research findings.